Operation Auxiliary Support System for FAO Lines Based on Key Operational Information - WU Min (Chengshi guidao jiaotong yanjiu)
Objective Currently, FAO (fully automatic operation) line operational control commands are issued through independent specialized systems with no synergetic collaboration mechanism among them. To ensure consistency in information acquisition and efficiency in synergetic response among personnel in various positions on FAO lines, it is necessary to establish an operation auxiliary support system based on key operation information, and build a multi-position collaboration platform to enhance the operational safety management and control level of FAO lines. Method Starting from requirement analysis, the overall architecture of the operation auxiliary support system is introduced, and the functions of this system are elaborated in detail. Recommendations for the future networked construction of operation auxiliary support system are provided based on related planning. ［Result & Conclusion］ Based on key operational information from various specialties and relying on intelligent analysis and collaborative linkage engine technology, the operation auxiliary support system for FAO lines enables information sharing and synergetic response across multiple positions. It facilitates efficient communication and mutual control among the control center, stations, and train multifunctional teams, thereby significantly improving the efficiency of fault emergency response.